PENGENDALIAN MUTU STATISTIK PRODUK AKHIR PAPERBOARD (STUDI KASUS PT SURYA PAMENANG KEDIRI JAWA TIMUR) - Azimmatul Ihwah dan Burhan Rafid Ekatama (Jurnal Teknologi Industri Pertanian, 2019)
Product quality control is an effort to minimize defective products from products produced by the company. Without the control of product quality, it will cause a large loss for the company, because irregularities are not known so that repairs cannot be carried out and eventually irregularities will be sustained. Paper are the most common products around us. One of the paper manufacturing industries in Indonesia is PT. Surya Pamenang. The purpose of this study was to determine whether the final product of paperboard was controlled statistically in quality. Quality control statistics were carried out using Pareto Diagram,  Control Chart and Fishbone Diagram. Data were taken in December 2017 and January 2018. Samples were carried out every one reel from each cardboard to the end of the Board Making unit. Then, the smoothness test from Back Side (BS) and Printing Side (PS) was conducted. From the Pareto diagram obtained 80% of the most types of disability, namely the Smoothness level of the high PS paper surface with a value of 10, the surface color of the bluish PS paper with a value of 8 and bowl with a value of 7. The control map results showed that the smoothness quality parameter at PS was still really need attention from the company, because in successive months these parameters indicate that the quality was not statistically controlled. The results of the analysis of causes of disability on paperboard were personnel, machines, material, and environment.Keywords: control chart, fishbone diagram, paperboard, pareto diagram, statistical quality control